EUROPEAN AGRICULTURAL CLUSTERS: HOW CAN EUROPEAN AGRICULTURAL CLUSTERS BE MEASURED AND IDENTIFIED? - Looijen, Arnold; Heijman, Wim (Economics of Agriculture, 2013)
This article contains a research into the agricultural clusters of the EU. The clusters are identified on the level of NUTS1 regions. The agricultural clusters are identified by main type of farming and by their contribution to the regional gross value added.